2021
DOI: 10.3389/fnbeh.2020.598812
|View full text |Cite
|
Sign up to set email alerts
|

Putative Activation of the CB1 Cannabinoid Receptors Prevents Anxiety-Like Behavior, Oxidative Stress, and GABA Decrease in the Brain of Zebrafish Submitted to Acute Restraint Stress

Abstract: Anxiety disorder is a well-recognized condition observed in subjects submitted to acute stress. Although the brain mechanisms underlying this disorder remain unclear, the available evidence indicates that oxidative stress and GABAergic dysfunction mediate the generation of stress-induced anxiety. Cannabinoids are known to be efficient modulators of behavior, given that the activation of the cannabinoid receptors type-1 (CB1 receptors) induces anxiolytic-like effects in animal models. In the present study, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Thus, it appears that the 9-minute net stress protocol was not sufficient to elicit prototypic stress responses in the current study. Future studies examining the impact of clomipramine treatment on acute stress responses should use a more severe stressor, such as acute restraint stress ( Ghisleni et al, 2012 ; Lucas Luz et al, 2020 ), that consistently increases cortisol and alters top exploration in individual zebrafish. Alternatively, other physiological measures of stress could be used in future studies to compliment whole-body cortisol levels, such as brain levels of corticotropin-releasing hormone (CRH) mRNA ( Ghisleni et al, 2012 ) or c-fos levels ( Ariyasiri et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it appears that the 9-minute net stress protocol was not sufficient to elicit prototypic stress responses in the current study. Future studies examining the impact of clomipramine treatment on acute stress responses should use a more severe stressor, such as acute restraint stress ( Ghisleni et al, 2012 ; Lucas Luz et al, 2020 ), that consistently increases cortisol and alters top exploration in individual zebrafish. Alternatively, other physiological measures of stress could be used in future studies to compliment whole-body cortisol levels, such as brain levels of corticotropin-releasing hormone (CRH) mRNA ( Ghisleni et al, 2012 ) or c-fos levels ( Ariyasiri et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The increasing concentration of S‐100β might participate in nerve damage and apoptosis by activating an oxidative stress reaction 25 . Previous studies showed that oxidative stress was correlated with anxiety‐like behaviour after acute stress 26–28 . In addition, as a marker of the integrity of the blood–brain barrier, S‐100β has proved to be associated with blood–brain barrier damage 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the axons of oxytocin neurons innervated the telencephalon and thalamus in adult zebrafish ( Figure 5 C,G, respectively). The telencephalon of fish is believed to be homologous to the mammalian limbic system, which controls anxiety, emotion, and motivation [ 77 ]. In zebrafish, the activation of cannabinoid receptor type-1 (CB1 receptor) in the telencephalon decreased anxiety from acute restraint stress [ 78 ].…”
Section: Discussionmentioning
confidence: 99%